Validation of Albumin Prescription in Vali Asr and Ayatollah Musavi Zanjan Hospitals - Rasool Markazi; Ali Pezeshkian; Fatemeh Ahmadi; Masoud Asadi-Khiavi; Maryam Noubarani (Tehran University of Medical Sciences, 2024)
Background: Human serum albumin (HSA) is a versatile protein exclusively produced by hepatocyte cells in the liver, constantly released into the bloodstream. Substantial quantities of HSA are employed to ameliorate a variety of clinical conditions. The purpose of this study was to assess the accuracy of albumin serum administration as recorded in the patient files of Valiasr and Ayatollah Mousavi Hospitals in Zanjan, Iran. methods: This study aimed to assess the accuracy of albumin prescriptions in adult departments of Ayatollah Mousavi and Valiasr hospitals from March 2013 to March 2019. Collected data on albumin consumption and patient information were carried out through reviewing medical records of patients, resulting in a selection of 316 cases. The study developed a reference framework for assessing albumin administration accuracy. A scoring mechanism was used to categorize prescriptions into appropriate, inappropriate, questionable, and ambiguous classes. Statistical analysis was conducted using SPSS software. Results: The findings indicated that the average patient age was 62.2 years. Among 316 patients, 60.4% were male. The mean serum albumin level measured 3.14 g/dL. The collective volume of albumin administered to patients across both hospitals was 5016 units, averaging 15.77 units per patient, and this was utilized over a total of 2253 days. Among the studied patients, 197 passed away during treatment, 110 were discharged, and 9 were transferred to other wards. Based on the established reference, it was observed that 5.5% of prescriptions were accurate, 51.9% were inaccurate, 26.4% were debatable, and 0.6% were undetermined. The total cost of prescribing this quantity of albumin in both hospitals amounted to 9,274,584,000 Rials, distributed as 8,347,125,600 Rials and 927,458,400 Rials in their respective proportions. Conclusion: Ultimately, the study highlighted that physician-prescribed albumin, guided by provided instructions, contained numerous errors necessitating vigilant and ongoing oversight. After a comprehensive review of all the data presented, it is apparent that there is no conclusive evidence supporting the existence of a formalized strategy for consistent reduction in albumin consumption within the hospitals.